2021
DOI: 10.5194/esd-2021-80
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends and Uncertainties of Regional Barystatic Sea-level Change in the Satellite Altimetry Era

Abstract: Abstract. Ocean mass change is one of the main drivers of present-day sea-level change (SLC). Also known as barystatic SLC, it is driven by the exchange of freshwater between the land and the ocean, such as melting of continental ice from glaciers and ice sheets, and variations in land water storage. While many studies have quantified the present-day barystatic contribution to global mean SLC, fewer works have looked into regional changes. This study provides a comprehensive analysis of regional barystatic SLC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The mass component of sea level can be inferred by subtracting the steric contribution from the observed sea level, or more recently (since the launch of the GRACE mission in 2002) from gravimetry measurements. Nevertheless, the gravimetry data have a coarse resolution of 300 km [20] and therefore cannot be used for local or even regional studies. For instance, in the case of the Mediterranean Sea, the authors of [19] found that while these data could be used to infer the mass component for the whole Mediterranean Sea, they were not suitable for smaller spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…The mass component of sea level can be inferred by subtracting the steric contribution from the observed sea level, or more recently (since the launch of the GRACE mission in 2002) from gravimetry measurements. Nevertheless, the gravimetry data have a coarse resolution of 300 km [20] and therefore cannot be used for local or even regional studies. For instance, in the case of the Mediterranean Sea, the authors of [19] found that while these data could be used to infer the mass component for the whole Mediterranean Sea, they were not suitable for smaller spatial scales.…”
Section: Introductionmentioning
confidence: 99%